Optimism and pessimism mediate the association between parental coronavirus anxiety and depression among healthcare professionals - Al-Anzi, Zainab Shalal (Journal of Educational and Psychological Sciences, 2024)
The current research aims to identify the mediating role of optimism and pessimism in the relationship between parental anxiety about the Corona virus and depression among parents working in health care in Saudi Arabia during the Covid-19 epidemic, on a sample consisting of (212) between the ages of (22 and 61), including (105) doctors and (107) nurses working in the health sector, during which the correlational approach was used. The results showed: that parental anxiety about the Coronavirus has a significant predictive effect on optimism, pessimism, and depression, and that optimism and pessimism also have predictive effects on depression, and optimism mitigated the negative effect of parental anxiety on health care about the Coronavirus; The results indicated that there is a statistically significant negative correlation between parents’ anxiety about the Coronavirus and optimism, and a statistically significant positive correlation between children’s anxiety about the Coronavirus and pessimism. The results also indicate that optimism is an essential source in reducing symptoms of depression in the face of parents’ experiences. For the Corona virus; The results indicated a negative correlation between optimism and depression, while the results indicated a positive correlation between pessimism and depression. The results also showed that optimism partially mediates the effect of anxiety about the Coronavirus on depression among parents in health care. The results showed a statistically significant direct effect of parents’ anxiety about the Coronavirus on depression, accompanied by a statistically significant indirect effect of parents’ anxiety about the Coronavirus on depression via optimism, which indicates that optimism mediates the relationship between the two variables partially. The research recommended the need for health institutions to intensify courses that contribute to alleviating the stress of their employees, working on positive thinking, as well as paying attention to strategic planning to manage health institutions safely in times of crises.
Keywords: parental anxiety; predictive effect; partial mediation; parents’ experiences of coronavirus; nurses